Về một phương pháp điều khiển truy nhập trong cơ sở dữ liệu - Hạnh, Đào Thị Hồng (Journal of Computer Science and Cybernetics, 2016)
A new access control sheme for information protection system is proposed. It assigns every legal user just on  interger key in such  a way that employing a simple formula to the key of the user subject and the ID number of the resource object yields the corresponding access right in the protection system. In the article also has given a concept of access control and grouped key. The described method is applied to relational database for implementing a single key that achieves access control in it.